The expression "five minus x" represents the subtraction of the variable x from the number five. Since x is a variable, its value is unknown and could vary. Therefore, the result of the expression "five minus x" would also vary depending on the value assigned to x. In algebraic terms, the expression can be written as 5 - x.
By factoring I get x-3 divided by x+3
x={5/3, -1} The equation factors into: (3x-5)(x+1)
-5 - (-5) = 0
If you say so!
52
By factoring I get x-3 divided by x+3
It is 5 - x. It depends what x is.
(x - 5)(x^2 + 1)
x2-5x-36 = (x-9)(x+4) when factored
x squared plus 5
54.3 squared
5x2 - 27x - 18 = (5x + 3)(x - 6)
(x - 5)(x + 5)
x = 7
15.
(x-1)(x-5)=x^2-6x +5 Because it is negative 5, I dont see an answer.
X/4-5